Cities, Monuments and Objects in the Roman and Byzantine Levant Studies in Honour of Gabi Mazor - Atrash, Walid; Overman, Andrew; Gendelman, Peter (2023)
Cities, Monuments and Objects in the Roman and Byzantine Levant celebrates Gabriel Mazor and his lifetime of work at the monumental city of Nysa-Scythopolis, Bet Sheʼan Baysān. This metropolis, part of the storied Decapolis, or league of ten cities, that flourished during the Hellenistic, Roman-Byzantine and very early Islamic periods until the devastating earthquake of AD 748, has been the singular focus of Gabi Mazor for a generation. The excavations, conservation and reconstruction at the site, and the detailed publications all are deserving of praise and appreciation.Chapters by leading archaeologists in Israel and the Levant explore themes and sites, in most cases by the chief archaeologists themselves, providing the latest information and insights about cities and villages from the Hellenistic to early Islamic periods across the region. This rare assemblage of scholars offers new material and interpretations of many of the key archaeological sites active today. The result is a rich trove of up-to-date data and insights that will be a must read for scholars and students active in this part of the ancient Mediterranean world.